ANALISA PERBANDINGAN EFESIENSI PENGGUNAAN ENERGI LISTRIK ANTARA SUPPLAI LISTRIK PLN DAN GENSET DI RSU MUHAMMADIYAH SUMATERA UTARA - Indra Roza; Agus Almi; Anas Dary Arinto; Pratowo Aji (Jurnal Simetri Rekayasa, 2020)
Energy distribution of electricity to consumers are sometimes susceptible to interference, both internal and external threats. Due to a disturbance sometimes consumers feel particularly aggrieved General Hospital because it can disrupt the operational process including Muhammadiyah General Hospital. Therefore, a lot of the General Hospital that use generators as a backup energy when there is a sudden interruption of PLN. However, for the operation of the generator and energy costs are not small. This study aims to determine how much energy use efficiency ratio of the electric generator to the electricity energy in terms of technical and economical at the General Hospital in the North Sumatra Muhammadiyah Mandala By Pass Medan. Given the comparative assessment, expected General Hospital, North Sumatra Muhammadiyah can make efficient use of electrical energy so as to reduce financing for the electricity.